2021
DOI: 10.1039/d1sc02690a
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of isostructural hydrogen-bonded organic frameworks: limitations and possibilities of pore expansion

Abstract: Library of isostructural porous frameworks enables systematic survey to optimize the structure and functionality of porous materials. Contrary to metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), a handful of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 43 publications
(63 reference statements)
1
47
0
Order By: Relevance
“…Time-resolved ps studies under 371 and 515 nm excitation revealed comparable mu tiexponential photobehavior, with lifetimes of 160-180 ps, 710-720 ps, and 2.3-2.5 n Modification of the arms of CBPHAT-1a with 1,2-diphenylethyne and 4,7-diphenylbenzo-2,1,3-thiadiazole resulted in the formation of more expanded HOFs (TolHAT-1 and ThiaHAT-1) [111]. Particularly, ThiaHAT-1 (Figure 6) showed a great stability up to 305 • C and a high BET surface area of 1394 m 2 g −1 , with a pore diameter of 15.5 Å.…”
Section: Hofs Based On Hexaazatriphenylene (Hat) and -Naphthylene (Ha...mentioning
confidence: 94%
See 1 more Smart Citation
“…Time-resolved ps studies under 371 and 515 nm excitation revealed comparable mu tiexponential photobehavior, with lifetimes of 160-180 ps, 710-720 ps, and 2.3-2.5 n Modification of the arms of CBPHAT-1a with 1,2-diphenylethyne and 4,7-diphenylbenzo-2,1,3-thiadiazole resulted in the formation of more expanded HOFs (TolHAT-1 and ThiaHAT-1) [111]. Particularly, ThiaHAT-1 (Figure 6) showed a great stability up to 305 • C and a high BET surface area of 1394 m 2 g −1 , with a pore diameter of 15.5 Å.…”
Section: Hofs Based On Hexaazatriphenylene (Hat) and -Naphthylene (Ha...mentioning
confidence: 94%
“…Remarkably, the CBPHAT-1a/HCl interactio (adsorption, desorption) was reversible even at ambient temperature. Modification of the arms of CBPHAT-1a with 1,2-diphenylethyne and 4,7-diph nylbenzo-2,1,3-thiadiazole resulted in the formation of more expanded HOFs (TolHAT and ThiaHAT-1) [111]. Particularly, ThiaHAT-1 (Figure 6) showed a great stability up t 305 °C and a high BET surface area of 1394 m 2 g −1 , with a pore diameter of 15.5 Å. Th photophysical properties of Tol-HAT-1 and ThiaHAT-1 were elucidated by steady-sta and time-resolved spectroscopy, as well as single-crystal fluorescence microscopy.…”
Section: Hofs Based On Hexaazatriphenylene (Hat) and -Naphthylene (Ha...mentioning
confidence: 99%
“…There are several advantages associated with various isostructural hexagonal networks (HexNets) of C3-symmetric carboxylic acids with p-conjugated cores. A key factor is the mosaic of materials has been formed using 1,2-diphenylethyne (tolane) and 4,7-diphenylbenzo-2,1,3-thiadiazole, which defines the relationship of carboxy-phenyl and -biphenyl arms [ 117 ].…”
Section: Photoswitchable Control Of Supramolecular Organic Systemsmentioning
confidence: 99%
“…Therefore, supramolecular complexes self-assembled through intermolecular hydrogen-bonding interactions, named HOFs, have been proven to be a potentially tunable platform for constructing functional materials [4][5][6][7]. So far, various supramolecular HOFs, made by employing organic molecules, have been reported and employed in fields like sensing, capture, separation, proton conductivity, catalysis, and so on [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%